Orange photoluminescence emission of samarium ion doped in calcium zirconium orthophosphate. Issue 4 (21st April 2021) - Mohan Prakash, Y. H.; Prakash Babu, D.; Madesh Kumar, M.; Ponkumar, S.; Mani Rahulan, K.
Abstract: Here we report on Orange Photoluminescence emission of samarium ion substituted calcium zirconium phosphate prepared by solid state reaction method. To study the crystal structure and phase transitions, the sample have been characterized by X-ray diffraction technique. The structure was orthorhombic with space group P 2 1 2 1 2 1 . The morphology, composition and functional group were characterized by using various analytical techniques such as Scanning electron microscopy, Fourier transform infrared spectroscopy and energy dispersive X-ray. These phosphors show orange emission when excited by 400 nm ultraviolet light. The luminous mechanism of prepared phosphor were analyzed and presented in this report.